DAMPAK LINGKUNGAN KERJA TERHADAP MOTIVASI KERJA PERAWAT RUMAH SAKIT UMUM DAERAH AHMAD YANI KOTA METRO - Department, administratio; Setioko, Sigit (Jurusan Ilmu Administrasi Publik, Universitas Lampung, 2017)
ABSTRACT. Suspected environment and unhealthy working conditions is an additional burden of employment for employees. Using a quantitative approach with data collection techniques using aquestionnaire researchers conducted a study of the impact of work environment on the motivationof nurse work in Ahmad Yani Hospital, Metro City. The result of research are: (a) From result of dataanalysis using Product Moment formula obtained value 0,13 <from value r table significance level 5%= 0,308 1% = 0,389 at N = 41. This indicates work environment has no impact on work motivationnurse at RSU A. Yani Metro City. (b) From the result of consultation with correlation value, it isknown that the value of 0.13 lies between the correlation range of 0.01 - 0.29 which shows the lowcorrelation. Thus it can be seen that the impact of work environment on the motivation of nursework in RSU A. Yani Metro City in low category. (c) The working environment has no impact on nursework motivation in RSU A. Yani Metro City. This means that environmental impacts such as lack oflighting and noise caused by patients and visitors have no significant impact on the motivation ofnurses of RSU A. Yani Metro. Nurses continue to perform their duties as usual despite the noise ofpatients and visitors. Keywords: working environment; work motivation